Geostrategi pertanian tembakau di Madura: Dinamika kualitas tembakau dan akses ekonomi - Nurfadilla, Siti (Maliki Interdisciplinary Journal, 2025)
Tobacco is one of the stepping stone commodities for farmers on Madura Island. Tobacco has a high economic value and is usually the main source of income for some farmers. The quality of Madura tobacco is not stable, many factors influence it, such as geographical conditions, weather, and different planting methods in each region. On the other hand, farmers' access to markets, capital, and information is not evenly distributed. This study aims to see how the current geostrategy of tobacco farming in Madura affects the quality of tobacco and the economic access of farmers. The results of the study concluded that locations with fertile soil and a supportive climate usually produce high-quality tobacco but farmers in the area may not have adequate access to markets or prices that are profitable for them. The tobacco trading system that is still controlled by middlemen also weakens the bargaining position of farmers. Therefore, a fairer and more equitable strategy is needed in managing tobacco farming to improve farmer welfare and ensure the quality of Madura tobacco remains guaranteed.